Re-deflning the Victorian Ideal: the Productive Transnormative Family in Sensation Fiction - Lane, Eva (My University, 2009)
This study examines two of the most popular sensation novels of the 1860s, Lady Audley's Secret by Mary Elizabeth Braddon and East Lynne by Ellen Wood, and their respective treatments of the Victorian family. Building on the work of critics who question and challenge the cohesiveness of the domestic ideal and the complete family within Victorian ideology, this project explores the representation of family units in both novels that are somehow beyond the ideological normative family of husband, wife and biological children. I examine several different figures, including the stepmother, the governess, the orphaned child, the single parent, and the unmarried aunt in order to trouble the distinction between the normative family and the transnormative family and thereby suggest that the contradictions and tensions that exist within a family grouping can function as enabling rather than debilitating. Through such an examination, I redefine the domestic ideal as ultimately flexible and adaptable rather than fleeting, frail or unachievable.
Keywords: English Language and Literature; English Language and Literature